PHARMACIST PROFESSION STUDENT PERCEPTION ABOUT PHARMACIST ROLE IN PHARMACY, COMMUNITY HEALTH CENTER AND HOSPITAL - Kadek Nadia Martha Dewi; Made Ary Sarasmita; Luh Putu Febryana Larasanty (Journal Pharmaceutical Science and Application, 2020)
Background: Pharmacists play a role as a part of health services both at pharmacies, hospitals and community health centers. Pharmaceutical care was regulated in the Regulation of the Minister of Health of the Republic of Indonesia. In the internship, students of the Pharmacists program Faculty of Mathematics and Natural Sciences, Udayana University can see clearly how the implementation of the role of Pharmacists in the Pharmacy, Hospital and Community Health Center. Objective: This study aims to assess the perceptions (responses) of Pharmacist students on the role of Pharmacists in various pharmacy services. Methods: This study used a one-group posttest only design methods. The population of the study used all of the Pharmacist students who were internship at the Pharmacy, Community Health Center and Hospital. The research instrument used a closed-ended questionnaire about the perceptions of Pharmacist students on the role of Pharmacists in internship locations. Results: The results showed that the role of pharmacists in pharmacies and community health centers was greater in the field of clinical pharmacy services. While in hospitals, pharmacists have a greater role in the field of drug management. Conclusion: Students have a positive perception of the role of pharmacists. There were no significant differences in perceptions of Pharmacist students on the role of Pharmacists in the field of drug management and clinical pharmacy services (p> 0.05). Keywords: pharmacist; pharmaceutical care; perception; role; students